So Close, Yet So Far Away: The Paradox of Status and Distinction among Instagram Influencers - Newlands, Gemma; Lutz, Christopher (AoIR Selected Papers of Internet Research, 2017)
Founded in 2010 as a platform for image-based sharing among friends, Instagram has evolved into a locus of economic activity due to the emergence of ‘Influencer marketing’. Some users monetise their followers by integrating sponsored ‘advertorials’ into posts. By cultivating a façade of honesty when making product recommendations to their audiences, Influencers leverage their perceived intimacy and relatability into profit. Influencers largely frame their success as merely the result of self-motivated perseverance. However, this framing obscures the offline-capital necessary for emulation. In line with previous research, we propose that Instagram is a highly unequal platform, reproducing or even reinforcing status hierarchies. Our contribution explores the paradoxical nature of the ‘Instagram Influencer’: they require different forms of capital to succeed but must suggest counterfactually that there is only limited distinction between them and their personal audience. To investigate this paradox, we conducted a mixed-methods empirical investigation in February 2017, relying on user-generated data. Firstly, Instagram posts were compiled (n=14,555) from two hashtags, #sponsored and #sponsoredpost. An initial social network analysis was carried out on this data. Secondly, 50 Influencer accounts were selected based on network centrality. Textual and visual data was collected from each account for in-depth qualitative coding. The data analysis revealed a proliferation of markers of socio-economic elevation, suggestive of the offline-capital necessary to succeed. However, corresponding to the need for Influencers to maintain relatability, there was limited ostensible distinction in the data. Instead, Influencers used language suggestive of intimacy and friendship, sharing their success with their followers.